Cardiovascular health knowledge and preventive practices in people living with HIV in Kenya - Temu, Tecla M. (BMC Infect Dis, 2015)
BACKGROUND: Traditional cardiovascular disease (CVD) risk factors contribute to increase risk of CVD in people living with HIV (PLWH). Of all world regions, sub-Saharan Africa has the highest prevalence of HIV yet little is known about PLWH’s CVD knowledge and self- perceived risk for coronary heart disease (CHD). In this study, we assessed PLWH’s knowledge, perception and attitude towards cardiovascular diseases and their prevention. METHODS: We conducted a cross-sectional study in the largest HIV care program in western Kenya. Trained research assistants used validated questionnaires to assess CVD risk patterns. We used logistic regression analysis to identify associations between knowledge with demographic variables, HIV disease characteristics, and individuals CVD risk patterns. RESULTS: There were 300 participants in the study; median age (IQR) was 40 (33–46) years and 64 % women. The prevalence of dyslipidemia, overweight and obesity were 70 %, 33 % and 8 %, respectively. Participant’s knowledge of risk factors was low with a mean (SD) score of 1.3 (1.3) out of possible 10. Most (77.7 %) could not identify any warning signs for heart attack. Higher education was a strong predictor of CVD risk knowledge (6.72, 95 % CI 1.98-22.84, P < 0.0001). Self-risk perception towards CHD was low (31 %) and majority had inappropriate attitude towards CVD risk reduction. CONCLUSION: Despite a high burden of cardiovascular risk factors, PLWH in Kenya lack CVD knowledge and do not perceived themselves at risk for CHD. These results emphasis the need for behavior changes interventions to address the stigma and promote positive health behaviors among the high risk HIV population in Kenya. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12879-015-1157-8) contains supplementary material, which is available to authorized users.